Assessment of the Campylobacter jejuni and C. coli in broiler chicken ceca by conventional culture and loop-mediated isothermal amplification method. (April 2017) - Sabike, Islam Ibrahim; Uemura, Ryoko; Kirino, Yumi; Mekata, Hirohisa; Sekiguchi, Satoshi; Farid, Ayman Samir; Goto, Yoshitaka; Horii, Yoichiro; Yamazaki, Wataru
Abstract: In a two-year survey of the 24 Japanese broiler chicken flocks at 9 farms from 2013 to 2014, C. jejuni/C. coli prevalence was assessed in a total of 131 slaughtered broiler chicken cecal samples by conventional culture methods and loop-mediated isothermal amplification (LAMP) assay. While 93 samples were C. jejuni / C. coli -negative, 38 (29.0%) showed Campylobacter loads of between 6.4 and 9.0 log CFU/g of ceca in conventional culture methods. The performance of LAMP assay was 100% accurate in terms of diagnostic sensitivity (38/38), specificity (93/93). Furthermore, LAMP assay enabled direct screening of C. jejuni and C. coli in cecal samples from broiler chicken chickens as rapid and cost-effective detection within 90 min and less than 1 US dollar, which can help monitor release of Campylobacter -contaminated chicken into the food chain, thereby reducing the incidence and public health risk of campylobacteriosis. Seasonal changes in C. jejuni and C. coli prevalence in broiler chicken ceca were significantly correlated with the frequency of food poisoning incidents caused by these bacteria in Japan. Highlights: Campylobacter loads range between 6.4 and 9.0 log CFU/g in Japanese broiler ceca. A LAMP assay directly detects C. jejuni / C. coli in broiler ceca within 90 min. Sensitivity and specificity for LAMP were equal to conventional culture methods. Prevalence in the broiler flocks was correlated with the food poisoning frequency. High broiler prevalence is a crucial risk factor in food poisoning in humans.